Visual Culture in the Age of Artificial Intelligence: A Bibliometric Study: Mappin Collaborations and Emerging Topins - Silva-Marchan, Henry; Aguilar-Chuquizuta, Darwin; Pardo-Garcés, José; Armestar-Amaya, Alex (Street Art & Urban Creativity, 2025)
Contemporary visual culture is undergoing a profound transformation driven by artificial intelligence. This bibliometric study examines the scientific development of the field between 2014 and 2024, based on 93 articles indexed in Scopus. MASHA, VOSviewer, and Biblioshiny were employed to analyse co-authorship networks, thematic trends, publication sources, and geopolitical dynamics. The results reveal exponential growth since 2021, with a particular emphasis on computer vision, generative aesthetics, and cultural criticism. European contributions addressing perceptual biases and algorithmic authorship are especially prominent. The findings also indicate a concentration of knowledge in the Global North and limited representation from the Global South. The study provides a critical mapping of the field and proposes a transdisciplinary research agenda for scholars in the arts, digital humanities, communication, and data science. It further recommends future research adopting mixed-method approaches to examine the ethical, cultural, and symbolic implications of visual AI.